Cardiopulmonary Resuscitation CPR Quality Outcome of Patients with Cardiac Arrest by Using Robotics/ Artificial Intelligence in Hospitals - Talib, Hanadi Saad Bin; Almurashi, Afnan Abdaljabbar; Alzahrani, Khames T. (International Journal of Innovative Research in Medical Science, 2022)
Background: The life-saving procedure is required rapid and effective methods to keep patients survive. Some literature reviews demonstrate those robotic medical systems like the applications as chest compression manipulators, which applied to enhance the quality during cardiopulmonary resuscitation in hospitals and because the number of studies that talked about the importance of using robotics was few This paper will be discussed Using of robotics and artificial intelligence (AI) during cardiopulmonary resuscitation in hospitals focusing on the level of efficiency of the outcome based on systematic reviews studies. Methods: This is a systematic review is based on collecting all previous articles which were done on the using Cardiopulmonary resuscitation CPR quality outcome of Patients with cardiac arrest by using Robotics/ Artificial Intelligence in hospitals. Results: The review process involved determining the suitability of 46 publications. There were 22 papers that made it through the full text screening and into the final review. The purpose of this research was to assess and improve outcomes for patients with cardiac arrest using robotics/artificial intelligence during CPR in hospitals. Conclusion: Robots and artificial intelligence have created a device that can reduce the risk of saving patients. It is safe, affordable, and accessible in real time, and more precise instrumentation and controls can adapt the massage to the rigidity of the patient's rib cage or clinical presentation.